Individual factors associated with masticatory performance of complete denture wearers: A cross‐sectional study. (30th May 2019) - Leles, Cláudio Rodrigues; Oliveira, Talitha Maria Cabral; de Araújo, Sara Cristina; Nogueira, Túlio Eduardo; Schimmel, Martin
Abstract: Aim: The aim of this study was to assess whether differences in inter‐individual clinical and prosthodontic variables affect masticatory performance (MP) of edentulous subjects who received new complete dentures. Materials and methods: There were 204 edentulous participants who received new maxillary and mandibular complete dentures between October 2014 and March 2018 at a university clinic. MP was measured by a mixing ability test with a two‐coloured chewing gum for 20 and 50 chewing cycles. The outcome variable was the degree of colour mixing of the chewed gum, expressed by the variation of hue (VOH) and measured by electronic colourimetric analysis. Explanatory variables included gender and age, quality of the dentures, classification of edentulous ridges and prognostic features, time since the insertion of the new dentures and patient‐reported outcomes related to complete denture treatment. Bivariate correlation tests, multiple linear regression and a linear mixed model were used for data analysis. Results: Mean VOH values were 0.57 (±0.13) and 0.43 (±0.16) for 20 and 50 chewing cycles, respectively. Mixing ability was higher in females than in males for 20 ( P = 0.036) and 50 ( P = 0.006) chewing cycles. No effects on the patient‐reported outcome measures were observed. The time since denture delivery, gender, age and Prosthodontic Diagnostic Index (PDI) score were independently associated with masticatory performance at 20 and/or 50 chewing cycles. Overall masticatory performance tested by the linear mixed‐effect model confirmed that VOH value was negatively influenced by male gender, older age and shorter time since denture delivery. Conclusion: Masticatory performance seems to be improved with the continuous use of newly inserted dentures and negatively influenced by advanced age.